Bibliometric Analysis of Omnichannel Retailing: Mapping Research Trends and Future Directions - Judijanto, Loso (West Science Business and Management, 2025)
Omnichannel retailing has emerged as a transformative strategy in the retail sector, integrating online and offline channels to provide a seamless shopping experience. This study conducts a bibliometric analysis using data from Scopus and visualization techniques with VOSviewer to map the research landscape, trends, and future directions in omnichannel retailing. The findings reveal a significant increase in academic interest post-2020, driven by digital transformation and changing consumer behaviors. The keyword co-occurrence network highlights dominant themes such as customer experience, supply chain management, pricing strategies, and technological advancements. Additionally, the author and country collaboration networks identify key contributors and research hubs, with China and the United States leading in scholarly output. Despite progress in omnichannel research, gaps remain in areas such as sustainability, AI-driven personalization, and omnichannel adoption in emerging markets. This study provides valuable insights for researchers and practitioners, emphasizing the need for interdisciplinary collaboration and technological innovation to enhance omnichannel strategies.
Keywords: Omnichannel retailing; bibliometric analysis; VOSviewer; customer experience